(untitled) (ex æquo, 2023)
This paper considers the extent to which men and women with PhDs reconcile work and family life in boundaryless careers in academia. The paper is based on a study of European PhD graduates in social sciences and humanities. The paper identifies three features of boundaryless careers in academia (1) inter-organizational mobility (2) international mobility and (3) boundaryless working hours. The results showed that, whilst many people appreciated the autonomy in academic careers, the insecurity, long hours and need for mobility caused conflicts between work and family life. This affected both men and women, but, due to traditional gender roles, difficulties combining academic careers with families affected women disproportionately.